ASSESSING THE IMPACT OF SECOND PILLAR COMPONENT ON OLD AGE PENSION IN LITHUANIA - Medaiskis, Teodoras; Gudaitis, Tadas (Ekonomika, 2013)
Abstract. The aim of the study was is to evaluate the impact of a privately accumulated second pillar component on old-age pension. This evaluation is based on quantitative, statistical data and qualitative analysis of pension accumulation results in second pillar during the years 2004–2012. Three groups of different monthly wage size (low, medium, and high) earners are analyzed by calculating the accumulated amounts and old-age pension values of persons who joined and who did not join the second pillar pension funds in 2004 and who retired in the beginning of 2013. The pension reform success (or failure) is evaluated from the point of view of old age pension beneficiaries by comparison of gain or loss of all three groups of participants due to participation in second pillar pension funds. The results show that due to the longer life expectancy the capital accumulated by women in the second pillar does not exceed the present value of loss in the pay-as-you-go system. The comparison of “official” annuities exposes a more optimistic result for both genders of participants of fully funded private second pillar pension funds, but is not confirmed by commercial annuities. Key words: old-age pension, private second pillar pension funds, pension reform